UNDERSTANDING THE MEDIATING ROLE OF STRATEGY IN FOSTERING CORPORATE SUSTAINABILITY (CAHIERS MAGELLANES-NS, 2024)
The study delves into a newly bulging stream of corporate governance with respect to sustainability. The increasing prevalence of sustainability committees or sustainability officers in companies and the changing orientation of leaders towards sustainability is bound to manifest into the company strategies. Against this backdrop, the study investigates how such sustainability related governance influences the sustainability performance of companies by considering the mediating role of strategy. Panel data analysis is performed on the sample of 103 Indian companies for the period 2016-17 to 2021-22. The results reveal that sustainability related governance leads to better strategy index and this further enhances corporate sustainability performance. These empirical findings substantially contribute to the existing literature as the role of strategy has been undermined in previous research. Moreover, this study attempts to facilitate practitioners, policy makers and regulators in better configuration of organizations into the sustainability milieu.